The adaptation of Iban oral folk tale "Keling" in a narrative animation - Voon, Keith Lip Khiong (Universiti Malaysia Sarawak (UNIMAS), 2010)
The Iban is oral folk tale closely related to the Iban spiritual and conception of the mythological world. The objectives of this research are to identify the folk tales among Iban society, to analyze the Iban folk tales, to produce a narrative animation based on Iban folk tale, and lastly to validate th outcome of the animation. Based on the reseach, a short animation will be produced and adapted form one of the most ancient Uban tale in the oral tradition, 'Keling the Great Warrior of Panggau Libaru'. The animation captures both the richness of the Iban folklore as well as the idiom of the Iban language.